ELABORATE MOST PREDOMINANT DISEASES AND COMPLAINS THAT PRESCRIBED PANCHAKARMA IN MEDICAL TOURISM DOWN SOUTH OF SRILANKA - R Abeysooriya, *S.; S.B Nuwansiri, L.; Wickramarachchi, W.J (International Journal of Ayurveda and Pharma Research, 2016)
Medical Tourism refers to the rapidly growing practice of travelling across international borders to obtain healthcare. Quite apart from its tourism appeal Sri Lanka also boasts the highest literacy rate in the region and a strong heritage in Ayurveda medicinal treatments, adding to the countrys appeal as a top Asian destination for medical tourism. Ayurveda is as much ancient as the human civilization. The concept has inherited many an ideology along the passage of time. In Ayurvedic therapy, the physician diagnoses the root of the cause and treats it accordingly. Various factors which cause the diseases can be reversed or minimized using Ayurvedic treatment. And for thousands of years, the most popular method used to restore and rejuvenate tired bodies and weary souls has been Ayurveda. The main objectives were investigating predominant native, Age, gender and diseases which were instigated in Ayurveda treatments. In this survey, chosen genuine Panchakarma treatment clinic in Suriyalanka Ayurveda beach hotel at Matara (down south of Srilanka). Selected Group included 216 guests. Clinical details were extracted from individual clinical case records this clinic. Germans (93.98%), Russians (3.70%), British (0.92%), Americans (0.46%), Others (0.92%) are predominant natives. The leading gender was Female (72.68%) and top Age group was 50-60 years (32.40%). Details of analyzed shows Germans are the most predominant in Pancha karma curing. Females are most attracted gender to Ayurveda. Middle ages are most instigated age group to Ayurveda. Rejuvenation, Weight reduction, Burnout Syndrome (Excessive stress), Hyperlipidemia, Pre-menopausal syndrome, Skin diseases, Joint pains, the most predominant diseases and occasions prescribe Ayurveda Panchakarma in down south of Sri Lanka.